Epidemiological studies of gastro-intestinal nematode infections of beef cattle. Reared in a savannah area of the state of Mato Grasso, Brazil - Melo, Hermano J.H. de; Bianchin, Ivo (Pesquisa Agropecuaria Brasileira, 2014)
During a three-year period, the authors studied the epidemiology of gastrointestinal nematode infection in weaned Zebu calves, reared extensively in Savannah areas of Mato Grosso State, Brazil. Faecal egg counts (E.P.G.) coprocultures and necropsies were performed on two groups of calves, one naturally infected and the other treated every 14 days and allowed to graze for 30 days on infected pasture before slaughter. The most common nematode species found were: Haemonchus spp. (H. Contortus and H. similis), Cooperia spp. (C. pectinata and C. punctata), Oesophagostomum radiatum and Trichostrongylus axei. The E.P.G. data indicated that there were two peaks of egg production, one at the beginning and the other in the middle of the rainy season. Necropsy findings showed that during the dry period the adult worm burden is maintained at a high level whereas the number of infective larvae on the pasture seems to be low. A group of calves treated strategically with a broad spectrum anthelmintic had mean weight gains significantly higher (P < 0.005) than the non-treated calves. Based on these data a series of strategical drenches during the dry period are suggested, both to eliminate the worm burden during this critic period of the year and also to reduce the larval population on pasture at the beginning of the rainy season.